TEKNOLOGI PENGOLAHAN PRODUK BERBASIS JAMUR DI KAWASAN RAWAN BENCANA ERUPSI MERAPI - Agung Utama, Mutiara Nugraheni, Titin Hera WH, (Universitas Negeri Yogyakarta, 2014)
This activity aims to provide an alternative post-harvest oyster mushroomsand fungi that are capable of producing acceptable to consumers;provide consumers an alternative to products made from mushrooms andhas a long shelf life and open opportunities for the development of agribasedhome industry. Methods of activities conducted by discussions aboutthe characteristics of mushroom and mushroom and post-harvest handling;manufacture of products as well as product acceptance testing by the community,and the development of home industry with pricing and packagingas well as permitting a small industry. The products made are chips oystermushrooms, mushroom chips, shredded oyster mushrooms and oyster mushroomsnugget. Products can be accepted by the consumer based on the consumerpreference test. The timing of expired products ie chips mushrooms:4 months, 3 months shredded oyster mushroom and oyster mushroomnuggets, until at least 1 year (due to the frozen food) for oyster mushroomchips: Rp 6.300,-/200 grams, mushroom chips: Rp 6.300,- /200 grams,crackers Rp 5.000,00,-, sausage oyster mushrooms: 8300/100 grams andoyster mushrooms nugget: Rp 11,300, -/200 gram. Evaluate of sales showedthe product can be sell and accepted by consumer, it shows that in terms ofpackaging, the price, the product is acceptable to consumers.